Jean Calvin (1509-1564) – i 500-året for hans fødsel - Jørgensen, Ninna (Dansk Teologisk Tidsskrift, 2009)
This article offers an introduction to Calvin’s life and thought in the 500th anniversary of his birth. Attention is called to his self-understanding in the Commentary to the Psalms, which he refers to as an “anatomy of the soul”, well suited for prayer – a consideration, which was central in his theological outlook. Calvin’s Humanist background and engagement in the Reform movement, his exile and battles against enemies inside and outside the congregation are described, and a survey of his theology given along the lines of Institutio. This includes the “double recognition” of God as Maker and as Saviour, providence being an essential part of the first, predestination of the second. The life of the Christian is unfolded both as an individual and as a member of a congregation, which praises God in music. Finally the question of secular authority is discussed.